SPECTRUM OF LIPOSARCOMAS-A STUDY OF 106 CASES - Khan, Naveed; Din, Hafeez Ud; Hashmi, Shoaib Naiyar; Muhammad, Iqbal; Atique, Muhammad; Khadim, Tahir; Akhtar, Farhan (Journal of Ayub Medical College Abbottabad, 2014)
Background: Liposarcoma is a malignant tumour that arises in fat cells in deep soft tissue. This study was conducted to access the spectrum of liposarcomas Methods: This descriptive study was conducted at Armed Forces Institute of Pathology (AFIP), Rawalpindi from 1st January 2008 to 31st December, 2012 and included all the cases diagnosed as liposarcomas. Records of the malignant tumors of soft tissue that presented during this period were analysed and out of this spectrum of liposarcomas were studied. Results: A total of 19367 malignant tumours were diagnosed during study period. Out of these, 615 were malignant soft tissue tumours. Out of these 106 cases were liposarcoma with an overall frequency of 0.54% of the malignant neoplasm and 17.24% of soft tissue sarcomas .The age ranged from 26-85 years. Out of these 106 cases 77 were male and 29 were female with a male to female ratio of 2.6:1. The most common tumour seen was pleomorphic liposarcoma (42.5%) followed by myxoid liposarcoma (22.6%), dedifferentiated liposarcoma (19.8%) and well differentiated liposarcoma (15.1%). Fifty five (51.9%) of liposarcomas originated in lower extremity, the second most commonly involved site was upper extremity (22.6%) Conclusion: Pleomorphic Liposarcoma is the commonest liposarcoma of extremities and their frequency is much high in our population. Keywords: Malignant, Soft tissue sarcoma, Liposarcoma